Competition in Network Industries : Where and How to Introduce It - Klein, Michael; Gray, Philip (World Bank, Washington, DC, 2012)
If privatizing network industries is to bring lasting public benefits, governments should also attempt to introduce competition. The scope for such competition is growing with increasing deregulation and technological innovation. As technology continues to improve, the use of "smart markets"--computer-assisted auction systems to clear competitive but complex markets--is likely to become feasible for an ever-expanding group of products and countries. This Note outlines the opportunities for introducing network competition--competition for the market, competition over existing networks, and competition among networks. It briefly considers in each case whether it will become easier or more complicated. It looks at how these opportunities could be applied in different networks. And it concludes with some basic guidelines for introducing competition: 1) the more complex the network and the lower the sunk cost, the more value there is likely to be in introducing competition from other networks. 2) Where technical change is rapid, defining the bonds of natural monopoly will be more difficult and the dynamic benefits of competition will be large. 3) Where government capacity to be benevolently and efficiently recognize natural monopoly and establish barriers to entry is weak, entry probably should not be limited by policy.